IMPLEMENTASI KEGIATAN EKSPERIMEN PADA PEMBELAJARAN KONSEP RANGKAIAN LISTRIK UNTUK MENGURANGI MISKONSEPSI MAHASISWA - Theo Jhoni Hartanto (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
The purpose of this article was to: (1) describe the initial understanding of students to the concept of direct current electrical circuits (series and parallel) before learning activities; (2) describe the understanding of the concept of direct current electrical circuits (series and parallel) after implementing experimental activities. The study using pre-experimental one-group pretest-posttest design with a sample of this study was the first year Physical Education Program’ students of University of Palangka Raya for academic year 2015-2016, consisted 25 students. The concepts’ understanding of students before and after learning processes was analyzed by using the certainty of response index (CRI). Based on the result: (1) before the learning, the average percentage of students who misconceptions of 50.40%, 35.20 % did not understand the concept, and who understand the concept of only 14.40%; (2) After learning activities by applying the experiment, the average percentage of students who do not understand the concept of misconceptions and reduced respectively to 9.60% and 6.40%, while the students understand the concept of increasing to 84%. That is, learning activities by implementing this experiment can reduce misconceptions on Physical Education Program’ students of University of Palangka Raya, in particular on the concept of direct current electrical circuits (series and parallel) . Keywords: misconceptions, experiments activities, electritical circuit